2011
DOI: 10.1038/jid.2011.91
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing Demonstrates that Human Papillomavirus Is Not Active in Cutaneous Squamous Cell Carcinoma

Abstract: Beta-papillomavirus (β-HPV) DNA is present in some cutaneous squamous cell carcinomas (cuSCC), but no mechanism of carcinogenesis has been determined. We used ultra-high throughput sequencing of the cancer transcriptome to assess whether papillomavirus transcripts are present in these cancers. Sixty-seven cuSCC samples were assayed for β-HPV DNA by PCR, and viral loads were measured with type-specific qPCR. Thirty-one SCCs were selected for whole transcriptome sequencing. Transcriptome libraries were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 58 publications
8
74
2
Order By: Relevance
“…Transcriptome sequencing from cutaneous SCCs has also demonstrated low viral copy numbers for betaHPVs and a lack of transcripts potentially encoding oncogenic proteins, in contrast to alphaHPVs, which exhibit much higher viral copy numbers per cell (61). It is possible that unlike alphaHPVs, the betaHPV genome is generally not as strongly amplified during the last step of infection due to weaker enhancers in the LCR and the absence of important transcription factor recognition sites, such as SP-1 and TEF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing from cutaneous SCCs has also demonstrated low viral copy numbers for betaHPVs and a lack of transcripts potentially encoding oncogenic proteins, in contrast to alphaHPVs, which exhibit much higher viral copy numbers per cell (61). It is possible that unlike alphaHPVs, the betaHPV genome is generally not as strongly amplified during the last step of infection due to weaker enhancers in the LCR and the absence of important transcription factor recognition sites, such as SP-1 and TEF-1.…”
Section: Discussionmentioning
confidence: 99%
“…HPV is supposedly a risk factor for cSCC development. However, only half of cSCCs reveal HPV-DNA (6,26,27), whereas no HPV activity could be detected (28). Evidences show that HPV effects are boosted during actinic keratosis (29).…”
Section: Accepted For Publication 14 April 2013mentioning
confidence: 99%
“…While some studies have reported an increased risk of CSCC in immunocompetent individuals with HPV infection (32)(33)(34), other studies have failed to show a relationship between HPV and CSCC risk (35)(36)(37) with the exception of anogenital CSCC (38).…”
Section: Human Papilloma Virus (Hpv)mentioning
confidence: 99%